Gamma Irradiation for Preservation of Suruhan Herbs (Peperomia pellucida L. Kunth.) and its Bioactivity Against L1210 Leukemia Cells - Ermin Katrin Winarno; Susanto Susanto; Hendig Winarno (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Peperomia pellucida includes the Piperaceae family that has anti-cancer, anti-inflammatory, antioxidant, and anti-microbial activities. Microbes easily contaminate dry herbs during storage, so special handling is needed. One of the preservation techniques is using irradiation technology. This technique can be used to extend the shelf life of herbal medicinal ingredients. This research aimed to study the effects of irradiation on the anti-cancer activity of P. pellucida leaves. P. pellucida leaves' dried powder was irradiated at doses of 5, 7.5, 10, and 15 kGy. The anti-cancer activity test was carried out against L1210 leukaemia cells. The un-irradiated irradiated samples were macerated successively with n-hexane, ethyl acetate, and ethanol, then be concentrated. The ethyl acetate extract was fractionated using silica gel column chromatography, obtained seven fractions. Their IC50 values < 20 mg/mL, with fraction F4 was the most active fraction (IC50 1.9 mg/mL). The result showed that gamma radiation at doses of 5 - 15 kGy reduced their cytotoxic activity significantly. However, the fractions were still in the active category as anti-cancer (IC50 values were < 20 mg/mL).